1980
DOI: 10.2337/diacare.3.1.46
|View full text |Cite
|
Sign up to set email alerts
|

Glucose Tolerance and Blood Lipids in Bran-Fed Patients with Impaired Glucose Tolerance

Abstract: Thirty-eight patients (13 men and 25 women) with impaired glucose tolerance, aged 33--70 yr, underwent a dietary program adding 20 g of raw bran to their usual diet without changing their dietary habits. After 1 mo of treatment, the areas under the curves for glucose and insulin were reduced from 26,214 +/- 5618 to 24,529 +/- 5207 g/min (P < 0.001) and from 15,893 +/- 9714 to 12,440 +/- 7377 mU/min (P < 0.001), respectively, cholesterol was reduced from 234 +/- 40 to 212 +/- 29 mg/dl (P < 0.001), and triglycer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
1

Year Published

1983
1983
2016
2016

Publication Types

Select...
6
3
1

Relationship

0
10

Authors

Journals

citations
Cited by 66 publications
(28 citation statements)
references
References 0 publications
0
27
1
Order By: Relevance
“…The current study indicates that the same is also true for diabetic patients. Nevertheless, inthe long term other aspects of cereal fibre, as for example in wholemeal bread, may be beneficial [30].…”
Section: Discussionmentioning
confidence: 99%
“…The current study indicates that the same is also true for diabetic patients. Nevertheless, inthe long term other aspects of cereal fibre, as for example in wholemeal bread, may be beneficial [30].…”
Section: Discussionmentioning
confidence: 99%
“…This may at least partly explain controversial results of former studies, with some (e.g., 20) but not all (e.g., 21) indicating metabolic improvement after longer-term interventions with insoluble dietary fibers. We have previously shown that the insoluble fiber used in the current study caused slight, but significantly enhanced, colonic fermentation compared with control, as assessed by postabsorptive hydrogen breath concentrations (8).…”
Section: Hydrogen Breath Testmentioning
confidence: 95%
“…Interpretation of the results after interventions with unrefined whole grains is difficult because of the presence of other active ingredients, such as minerals, phyto-oestrogens and antioxidants [27]. Bran products, which showed improved glycaemic control in some [28,29] but not all [30] longer-term intervention studies, contain starch, protein and lipids in addition to dietary fibres.…”
Section: Introductionmentioning
confidence: 99%